High Density Lipoprotein (HDL) Level and Blood Urea Nitrogen (BUN)/Creatinin Ratio Relationship with One-Month Outcome in Acute Ischemic Stroke Patients - Habib Djarkoni, Ilham; Iqbal Basri, Muhammad; Akbar, Muhammad; Hamid, Firdaus; Kurnia Bintang, Andi; Tamasse, Jumraini (Journal of Society Medicine, 2023)
Introduction: Stroke has caused around 15.5% of all deaths. Evaluation of factors that worsen clinical outcomes is necessary to avoid complications such as renal dysfunction and secondary dyslipidaemia. This study aims to determine the relationship between increasing serum HDL levels and blood urea nitrogen–serum creatinine ratio (BUN/Cr) on clinical outcomes of acute ischemic stroke. Method: Prospective cohort study was used with subjects being first-onset acute ischemic stroke patients. Demographic, clinical data, and assessment of BUN/Cr and HDL ratios were collected. Subjects were divided into good clinical outcome (mRS 0-2) and poor clinical outcome (mRS 3-6) groups, and then analysed using multiple linear regression multivariate analysis with confidence interval of 95%. Results: 60 participants met the inclusion criteria. There was a significant relationship between serum BCR levels and poor clinical outcomes (p <0.001) relationship between serum HDL levels and poor clinical outcomes also shown significances (p <0.001) Mean BCR in good and poor clinical outcomes of acute ischemic stroke were (17.08±30.13) and (29.35±67.30) respectively. Mean HDL in good and poor clinical outcomes were (39± 62) and (41 ± 92) respectively. A multiple linear regression analysis showed a positive correlation (p <0.001) between increasing Serum HDL levels and Bun/Cr ratio simultaneously to poor clinical outcomes in acute ischemic stroke patients. The Cut-off point was 20.9 for BUN to creatinine ratio and 46 mg/dL at serum HDL. Both of BUN/Cr ratio and HDL were shown high specificity and could be used as predictors of clinical outcome in acute ischemic stroke patients. Conclusion: Increased BUN/Cr ratio and increased serum HDL levels were associated with clinical outcomes in patients with acute ischemic stroke.